Tools of a systematic approach in the implementation of the cluster initiative in real sector industries - Nurgalieva, S.Zh.; Arynova, Z.A.; Nygmanov, B.; Kaidarova , A.T. (BUKETOV BUSINESS REVIEW, 2023)
Abstract Object: substantiation of theoretical and methodological provisions and development of practical recommendations for the formation and effective implementation of a cluster strategy for managing the real sector of the economy at the regional level. Achieving this goal required solving a number of tasks, including: developing proposals for the formation of clusters in the real sector of the economy of the Pavlodar region; identifying and systematizing cluster strategies taking into account the specifics of industries; determining priorities for stable interaction of cluster entities in the real sector of the regional economy. Methods: many research tasks that require an analytical assessment of the innovative and investment activities of industrial enterprises of the region have formed a branch of its methodology. The latter considers the need to use the methods of system analysis and traditional statistical methods of comparative analysis in parallel. The theoretical basis of the provisions presented in the article included domestic and foreign research, as well as the work of scientists studying the problems of clustering and the main directions of cluster policy in the regional economy. Findings: one of the most important problems hindering the development of the innovation industry at the regional level is the low innovation activity of enterprises, since the majority of enterprises of the real sector of the region have a fairly high innovation potential. At the same time, in terms of technology transfer, these companies have little prospects in terms of interaction with enterprises of other sectors and sectors of the economy. The foregoing largely determines the timeliness of work aimed at identifying the main methods and priorities for the formation of group initiatives in the regional economy. The practical significance of the study lies in the specific proposals directed to increase the investment attractiveness of Pavlodar region and increase its innovative potential through the implementation of a number of cluster initiatives in the real sector. Conclusions: the results of the study made it possible to identify a number of recommendations on priority aspects of the implementation of cluster initiatives in the region in a particular industry context. This made it possible to identify priority areas for the development of the regional economy in the long term.